Uncertainty and perception of danger among patients undergoing treatment for prostate cancer. (18th September 2012) - Kazer, Meredith Wallace; Bailey Jr, Donald E.; Chipman, Jonathan; Psutka, Sarah P.; Hardy, Jill; Hembroff, Larry; Regan, Meredith; Dunn, Rodney L.; Crociani, Catrina; Sanda, Martin G.; ,
Abstract : Study Type – Therapy (attitude prevalence) Level of Evidence 2a What's known on the subject? and What does the study add? Marked differences in uncertainty among patients have been found relating to race and social environment indicating that as uncertainty increases, social functioning declines. Correlations have been found between uncertainty and patients' coping, psychological adjustment and perceptions of their health and illness. Studies suggest the detrimental effect of uncertainty among patients with prostate cancer in the perception of their quality of life. These studies underline the potential benefit of targeted intervention. The study provides a unique insight into the impact of uncertainty and perception of danger on overall satisfaction with treatment outcomes in men with prostate cancer. Its results suggest that possible disparities related to patient racial background and education may exist in the perception of cancer‐related uncertainty. Racial and educational disparities, coupled with a mild to moderate association of uncertainty or danger perception and overall outcome satisfaction, suggest an unmet need for healthcare and nursing services for men undergoing treatment for prostate cancer. OBJECTIVES:   To investigate patient uncertainty and perception of danger regarding prospects for clinical prostate cancer control.   To determine the impact of these factors on satisfaction with overall prostate cancer treatment outcome. PATIENTS AND METHODS:   Men who had undergone primary treatment for early stage prostate cancer and who were participants in the Prostate Cancer Outcomes and Satisfaction with Treatment Quality Assessment (PROSTQA) prospective cohort study of prostate cancer outcomes (the parent study) were offered the opportunity to participate in the present study.   Centralized phone interviews were conducted to determine patient‐reported uncertainty regarding cancer status (measured by the Mishel Uncertainty in Illness Scale‐Community Form), perception of danger (measured by Folkman and Lazarus' Appraisal Scale) and satisfaction with treatment outcome (measured by the Service Satisfaction Scale for Cancer Care). The study used the same centralized telephone interview centre as was used in the parent study.   Data were collected at 48, 60 or 72 months after the completion of prostate cancer treatment.   Relationships among measures were characterized by Spearman rank correlation coefficients ( r ). RESULTS:   A total of 338 agreed to participate, representing 76% of those who were invited.   Younger patients experienced less uncertainty ( r = 0.20, P < 0.001), yet reported greater perception of danger ( r =−0.12; P = 0.03) concerning their previously treated prostate cancer.   African‐American patients showed greater uncertainty than other ethnic groups ( P = 0.005) but did not have a greater perception of danger ( P = 0.36).   Education played a major role in uncertainty; patients with lower levels of education tended to report higher degrees of uncertainty ( r =−0.25; P < 0.001).   There was a mild to moderate general association between the three outcomes. A greater sense of uncertainty was associated with a greater perception of danger ( r = 0.34, P < 0.001), and as danger and uncertainty increased, satisfaction with treatment outcome tended to decrease ( r was between −0.30 and −0.34, P < 0.001). CONCLUSIONS:   Results suggest that possible disparities related to patient racial background and education may exist in the perception of cancer‐related uncertainty.   Racial and educational disparities, coupled with a mild to moderate association of uncertainty or danger perception and overall outcome satisfaction, suggest an unmet need for healthcare and nursing services for men undergoing treatment for prostate cancer.